Answer:
11) x=1 or x=3.
12) x=2/3 or x=-7.
Explanation:
So we have two equations:
![f(x)=3x(2x-6)\\f(x)=3x(x+7)-2(x+7)](https://img.qammunity.org/2021/formulas/mathematics/high-school/4u6o4cspb3yd7dv0ronys58sj5hty99b0v.png)
And we want to solve them. To do so, make each of them equal 0 and then solve for x:
11)
![f(x)=3x(2x-6)\\0=3x(2x-6)](https://img.qammunity.org/2021/formulas/mathematics/high-school/xh8p9c1up9bed80oh6sz8hldhwbfcg8pys.png)
Using the Zero Product Property, either one or both of the factor must be zero for this to be true. Therefore, make each factor equal to zero and solve:
![3x=0 \text{ or } 2x-6=0](https://img.qammunity.org/2021/formulas/mathematics/high-school/tyli7t9sjvaymzxnmiwcq5kz1a5ictirml.png)
Divide the left by 3. On the right, add 6 and then divide by 2:
![x=0\text{ or } 2x=6\\x=0 \text{ or } x=3](https://img.qammunity.org/2021/formulas/mathematics/high-school/51oy47n409ms6hnuq1yswzbk8wcp4v5u1t.png)
Therefore, the solutions to the first equation is:
x=1 or x=3.
12)
![f(x)=3x(x+7)-2(x+7)](https://img.qammunity.org/2021/formulas/mathematics/high-school/6ogiypbh8fd77u29yc5nx0hkzx85vr6zyz.png)
First, use the distributive property to group the terms together. The equation is equivalent to:
![f(x)=(3x-2)(x+7)](https://img.qammunity.org/2021/formulas/mathematics/high-school/zp4msrl6wlg7uy7ain2o96c1etd5br3b3o.png)
Now, set the function to zero and solve:
![0=(3x-2)(x+7)](https://img.qammunity.org/2021/formulas/mathematics/high-school/9ycr504zn867rkvjad1ymidn1g4i9qh527.png)
![(3x-2)=0 \text{ or } x+7=0\\3x=2 \text{ or } x=-7\\x=2/3 \text{ or } x=-7.](https://img.qammunity.org/2021/formulas/mathematics/high-school/zuf4f2z7o5iqmrs4rua1vp82yrvorqiy2z.png)
Therefore, the answer is:
x=2/3 or x=-7.